The Neurosteroid Allopregnanolone Modulates Specific Functions in Central and Peripheral Glial Cells - Faroni, Alessandro; Magnaghi, Valerio (Frontiers in Endocrinology, 2011)
Since the first observations on the existence of “neurosteroids” in the 1980’s, our understanding of the importance of these endogenous steroids in the control of the central and peripheral nervous system has increased progressively. Although most of the observations were made in neuronal cells, equally important are the effects that neurosteroids exert on glial cells. Among the different classes of neurosteroids acting on glial cells, the progesterone 5α-3α metabolite, allopregnanolone, displays a particular mechanism of action involving primarily the modulation of classic GABA receptors. In this review, we focus our attention on allopregnanolone because its effects on the physiology of glial cells of the central and peripheral nervous system are intriguing and could potentially lead to the development of new strategies for neuroprotection and/or regeneration of injured nervous tissues.